2009
DOI: 10.1007/s11999-008-0701-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CAND2 and WNT7a as Candidate Genes for Congenital Idiopathic Clubfoot

Abstract: Congenital idiopathic clubfoot is a common pediatric musculoskeletal deformity with no known etiology. The deformity reportedly follows a Mendelian pattern of inheritance. Recent work has demonstrated linkage in chromosome 3 and 13 in a large, multigeneration, highly penetrant family with idiopathic clubfoot. From the linkage region on chromosome 3, we selected the candidate genes CAND2 and WNT7a, which are involved in lower extremity development, and hypothesized mutations in these genes would be associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 11 publications
(13 reference statements)
0
12
0
1
Order By: Relevance
“…In addition, familial occurrence and interand intraphenotypic variability of clubfoot is well documented (Basit & Khoshhal, 2018). Several genes were identified as susceptible genes in clubfoot, such as the HOX family, CASP family, PITX-TXB4 pathway, troponin (TN) family, GLI3, T-box and MTHFR genes (Hecht et al, 2007;Shrimpton et al, 2004;Shyy et al, 2009;Weymouth et al, 2016;Zhang et al, 2016). However, these studies do not further explore abnormally active signaling pathways and potential upstream and downstream regulatory networks.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, familial occurrence and interand intraphenotypic variability of clubfoot is well documented (Basit & Khoshhal, 2018). Several genes were identified as susceptible genes in clubfoot, such as the HOX family, CASP family, PITX-TXB4 pathway, troponin (TN) family, GLI3, T-box and MTHFR genes (Hecht et al, 2007;Shrimpton et al, 2004;Shyy et al, 2009;Weymouth et al, 2016;Zhang et al, 2016). However, these studies do not further explore abnormally active signaling pathways and potential upstream and downstream regulatory networks.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic DNA was extracted from peripheral blood leukocytes using standard techniques. WNT7A gene was amplified by PCR and bidirectional sequence using previously described primers [Woods et al, 2006;Shyy et al, 2009]. Sequencing was performed using ABI Prism BigDye Terminator v3.1 Cycle Sequencing kit (Applied Biosystems, Foster City, CA) in an ABI 3130 Genetic Analyzer sequencer (Applied Biosystems).…”
Section: Molecular Analysesmentioning
confidence: 99%
“…In our laboratory, approximately 40 individuals with limb deficiencies were screened for WNT7A mutations (including the family reported in 2007 by Lonardo et al), and only the case reported here was positive. One group of researchers screened patients with the Zimmermann-Laband syndrome [Abo-Dalo et al, 2008] with negative results, and two other groups screened individuals with idiopathic talipes equino-varus (ITEV) and did not find indications of a role of WNT7A mutations [Liu et al, 2008;Shyy et al, 2009]. Thus, while the spectrum of WNT7A-associated phenotypes may not yet have been fully explored, mutations in WNT7A seem to be a very rare cause of limb reduction defects, and screening this gene may be warranted only in cases that present with the specific phenotypes of Al-Awadi-Raas-Rothschild or Fuhrmann syndromes.…”
Section: Molecular Basis Of the Aarr Syndromementioning
confidence: 99%